1 ANALISIS PERMINTAAN DAN PENAWARAN MAKANAN KHAS SALA BULEK DI PANTAI GANDORIAH PARIAMAN - Putri, Junita Sartika; Waryono, Waryono; Abrian, Youmil (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aims to analyze the market equilibrium between demand and supply is affected by six factors such as: the price, price of substitute goods, consumer income, the number of buyer, the cost of production, and the number of producers on the market.These types of descriptive quantitative research with survey method, population in this study was the visitors who buy specialities Sala Bulek and all of the Sala Bulek traders on the Gandoriah Beach. The research sample amounted to 10 consumers and 10 traders. The type of data used is primary data obtained through observation, interviews, documentation and questionnaire. The sampling technique is non-probability sampling with purposive sampling types. Then test the classical assumption of normality test and heterokedastistas using an Eviews7 and SPSS 16 application. The analisys tools is the model of simultaneous equations two stage least squeres method (2SLS). Next, define the market equilibrium through mathematical approach and chart/curve. After that Break event point analysis.The study found there is a equilibrium market between demand and supply that is affected by price (P), price of substitute goods (Ps), consumer income (Y), the number of buyer (N), the cost of production (C), and the number of producers on the market (Tp). Simultaneous equation analysis results the market equilibrium occurs when the IDR. 400 equilibrium price, and quantity of 550 pieces. And than Break Event Point (BEP) analyze result optained BEP (unit) of 260 units and BEP (rupiah) of IDR.130.000.Keyword: Demand, Supply, Sala Bulek,Equilibrium Market.